The Personality’s Responsibility as a Value - Marčenoka, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The modern society can be characterised by the rapid process of social and moral differentiation. Destruction and reassessment of traditional values, orientation of the modern personality to achievement and attainment of material benefits as leading values in human life caused the spiritual and moral crisis in the society, especially amongst teenagers. Responsibility as a value feature of a personality issues the challenge of the moral choice, which is expressed in the spheres of living, interests, needs and social relations, defining the meaning of life of every member of the society.